Pattern of eye disease among obese population in Erbil city, Iraq - Roaa Mikdad Nemat; Ahmed Kareem Joma (Zanco Journal of Medical Sciences, 2024)
Background and objective: Obesity is a multifactorial disease. It is a multifactorial pathology that can be related to an altered nutritional behaviour or secondary to genetic, hypothalamic, iatrogenic or endocrine diseases. Obesity and visual acuity are negatively correlated, obesity may be linked to dysfunction of the mechanical and vascular components of the eye. The aim of the study is to find out the impact of obesity on eye health and the pattern of eye disease.